Agro-morphological diversity of Bambara groundnut lines evaluated under field conditions. Issue 2 (15th March 2022) - Hlanga, Nokuthula; Modi, Albert; Mathew, Isack
Abstract : Assessing agro-morphological variation is important for crop improvement strategies in cultivated species. Bambara groundnut ( Vigna subterranea (L.) Verdc.) is a neglected crop that requires extensive agro-morphological characterisation to design suitable agronomic and crop improvement strategies. Nineteen Bambara groundnut lines were evaluated at two sites for agro-morphological traits in 2017 and 2018. The experiments were laid out as a split-split plot completely randomised design with three replications. The lines showed significant differences ( p < 0.05) for all the traits except chlorophyll content and stomatal conductance. The observed genotypic differences would be useful for Bambara groundnut improvement if they are underpinned by genetic differences for recombination. Principal components 1 and 2 accounted for 52.31% of the variation showing that agro-morphological traits alone could not adequately discriminate between the Bambara groundnut lines. The most useful traits were root and shoot mass, plant height and leaf number. The negative and unfavourable correlations between seedling emergency and chlorophyll would complicate simultaneous selection for these traits during Bambara groundnut improvement. However, genetic dissimilarity indices indicated that there was genetic variation within the germplasm, which is important for Bambara groundnut improvement. Lines Kenya Capstone, Uniswa-Red-G, Uniswa-Red-R and KANO2 were selected for breeding and recommended for production due to their high performance in several key traits.